2022
DOI: 10.1039/d2fo00185c
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG ameliorates deoxynivalenol-induced kidney oxidative damage and mitochondrial injury in weaned piglets

Abstract: Deoxynivalenol (DON) is a common mycotoxin that pollutes food crops and adversely affects the health of animals, even humans. Lactobacillus rhamnosus GG (LGG) can alleviate intestinal injury, anti-inflammatory and antioxidant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…In this study, a total antioxidant capacity assay to characterize DE111 ® activity was used. In this assay L. rhamnosus GG was used as a comparator strain as its antioxidant capacity has been previously reported (Ma et al, 2022). While, both DE111 ® and L. rhamnosus GG demonstrated antioxidant activity when measured by this assay, the levels varied significantly between the two strains (Figure 7).…”
Section: In Vitro Analysis Reveal Strong Antioxidant Capacity Of De111 ®mentioning
confidence: 77%
“…In this study, a total antioxidant capacity assay to characterize DE111 ® activity was used. In this assay L. rhamnosus GG was used as a comparator strain as its antioxidant capacity has been previously reported (Ma et al, 2022). While, both DE111 ® and L. rhamnosus GG demonstrated antioxidant activity when measured by this assay, the levels varied significantly between the two strains (Figure 7).…”
Section: In Vitro Analysis Reveal Strong Antioxidant Capacity Of De111 ®mentioning
confidence: 77%
“…Significant decreases in the proportion of the DNA synthesis phase were observed, accompanied by increases in the G1 phase, representing pre-DNA synthesis. Oxidative stress, caused by a mismatch between free radical production and cellular defense ability, has been confirmed as one of the cytotoxic effects induced by DON in existing studies [ 33 , 34 , 35 ]. It has been reported that RIOK1 was correlated with the transcription factor SKN-1, which is critical for oxidative stress resistance [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 98%
“…36 Polyunsaturated fatty acids in biological membranes can be attacked by oxygen radicals, causing lipid peroxidation. 37 As the final product of polyunsaturated fatty acid peroxidation in cells, MDA is widely regarded as a marker of oxidative stress. 37 Previous studies have shown that the level of T-AOC, GSH-Px, and SOD in the immune organs of chickens was decreased and the MDA content was raised by cold stimulation.…”
Section: Discussionmentioning
confidence: 99%